ISOLATE OF HETEROTROPHIC MICROALGAE AS A POTENTIAL SOURCE FOR DOCOHEXAENOIC ACID (DHA) - Julianti, Elin; Fathurohman, Mochamad; Damayanti, Sophi; Kartasasmita, Rahmana Emran (Marine Research in Indonesia, 2018)
Docosahexaenoic acid (DHA) is one of essential fatty acids that are beneficial to health. Nowadays, the source of docosahexaenoic acid (DHA) is mainly obtained from fish which are extracted into fish oil products. However, the fish oil products still have some drawbacks in term of purity, acceptable flavor for costumers, and also their not environmental friendly production process. As an alternative solution, heterotrophic microalgae can be used as a potential source for DHA due to their excellence compared to fish oil products. The aim of this study is to isolate the heterotropic microalgae that can produce DHA. The heterotrophic microalgae were isolated from mangrove fallen leaves (Rhizophora apiculata) by using direct planting method. The morphology of pure microalgae colony were observed through light microscope and subsequently fermented for 14 days. Fatty acids were extracted and methylated through direct transesterification method. Identification and quantification of DHA were conducted by using gas chromatography. The results were four isolates of heterotropic microalgae, namely MTKC1, MTKC2, MTKC3, and MTKC4. The extract of MTKC2 that only showed the content of DHA with value of 9.2 % w/w. Therefore MTKC2 is a potential source for DHA. The MTKC2 was further identified by using molecular biology method and confirmed as Thraustochytrium aureum.